Effects of pre-germination treatments and storage periods on germination, vigour, chemical and health composition of seeds of three cassava (Manihot esculenta Crantz) cultivars - Opoku, Priscilla Nana Ama (2017)
A thesis submitted to The School of Research and Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the award of Master of Philosophy Seed Science and Technology,